Isolation, characterization, and in vitro evaluation of bovine rumen submucosa films of collagen or chitosan-treated collagen. (January 2016) - Gopal Shankar, K; Udhaya Kumar, S; Sowndarya, S; Suresh Babu, P; Rose, C
Bovine rumen is hitherto considered as an inedible waste of meat industry. The rumen tissues can be used as an alternative source of collagen to produce biocompatible materials for clinical application. In an effort to develop a functional biomaterial from the inedible mammalian tissues, this study aims to isolate and characterize bovine rumen submucosa. Initially, the rumen tissue was sequentially processed using chemical and enzymatic treatment to decellularize, neutralize, stabilize, and to produce a native collagen matrix which is referred as collagen film (COL-F). Thus, prepared matrix was treated with 1% (w/v) chitosan solution to produce a hybrid film which is referred as collagen–chitosan film (COL/CS-F). The comparative study includes the evaluation of physical, chemical, and biological properties of the biofilms prepared. The surface topology of COL-F exhibited a continuous collagenous network with fibrous nature, while the chitosan treatment provided smooth plain surface to the parent film. Incorporation of chitosan in COL-F increased the tensile properties, as well as the thermal stability and durability of the films. The Fourier Transform Infrared spectroscopy results revealed the presence of respective amide peaks, which corresponds to protein (collagen), and the evidence of collagen–chitosan interlinking. The submucosa layer was electrophoretically found to have type I collagen. The X-ray diffraction data showed the presence of amorphous and crystalline peak which attributes to the triple helical structure of collagen in the films. Cytotoxicity studies on the films were performed in vitro using human keratinocytes. The results of cell viability and proliferation demonstrated that COL-F and COL/CS-F exhibit good biocompatibility and therefore can augment cell infiltration and proliferation. However, enhanced cellular activity was observed on the chitosan treated COL-F. These observations demonstrate that the biofilms prepared in this study can be used as an alternative functional biomaterial in tissue engineering.